Be quiet! - Higgins, Ryan T. (Los Angeles : Disney-Hyperion, 2017)
Rupert the mouse wants to star in an artistic, wordless picturebook, but his animal friends cause problems by talking too much.
Keywords: Animals -- Fiction; Books -- Fiction; Noise -- Fiction; JUVENILE FICTION / Animals / Mice, Hamsters, Guinea Pigs, etc; JUVENILE FICTION / Books & Libraries; JUVENILE FICTION / Humorous Stories; Humorous fiction